Electrochemical performance of SiCN embedded carbon (SiCN–C) fiber mat electrodes for lithium-ion battery: Electrospinning polysilazane in air or protective atmosphere - Heloisa Ramlow; Cintia Marangoni; Günter Motz; Gurpreet Singh; Ricardo Antonio Francisco Machado (Open Ceramics, 2023)
Here polysilazane/polyacrylonitrile fiber mats were manufactured by electrospinning in air or protective atmosphere. After pyrolysis, SiCN embedded carbon (SiCN–C) was tested as lithium-ion battery (LIB) electrode. Fibers electrospun in nitrogen are found to be thinner due to the slower solidification of the flying jet. XPS analysis confirmed that fibers electrospun in air incorporated a great oxygen content during shaping. The highest charge capacity of 773 mA h g−1 at 50 mA g−1 was recovered for SiCN–C electrospun in air. Oxygen increased the capacity due to its high character to attract Li+ ions, but SiCN–C electrospun in air suffered voltage hysteresis. Contrariwise, the SiCN–C electrospun in nitrogen demonstrated stable cycling with a charge capacity of 299 mA h g−1 and 98% recovery of the initial capacity due to enhanced free carbon content. These findings make electrospinning very promising for the highly controlled production of freestanding SiCN fiber mat electrodes.